Aerodynamic simulation of a blimp kind unmanned aerial vehicle for stable environmental conditions - López-Leyva, Josué Aarón; Aguilera, L.A.; Ponce Camacho, Miguel Ángel; Básaca-Preciado, Luis C.; Ramos García, Raúl; Ramos García, V.M. (My University, 2018)
An Unmanned Aerial Vehicle blimp kind prototype for stable environmental conditions is shown in this paper. The lift, drag, weight, and thrust parameters are analyzed on the basis of the Archimedes principle, Bernoulli and continuity equations, and fluid simulations for different conditions (low-speed wind and absence of turbulence). The calculated push force (lift) is the minimum value to produce sustentation considering the overall mass of the aircraft. On the other hand, the drag parameter was analyzed using the fluid simulation to visualize the drag force.
International journal of mechanical engineering and robotics research
Keywords: Lift; Drag; Fluid simulation; Unmanned aerial vehicle